The secret language of leadership how leaders inspire action through narrative - Denning, Stephen (San Francisco Jossey-Bass, 2007)
The book introduces the concept of narrative intelligence?an ability to understand and act and react agilely in the quicksilver world of interacting narratives. It shows why this is key to the central task of leadership, what its dimensions are, and how you can measure it. The book?s lucid explanations, vivid examples and practical tips are essential reading for CEOs, managers, change agents, marketers, salespersons, brand managers, politicians, teachers, parents?anyone who is setting out to the change the world.
Includes bibliographical references (p. 245-263) and index.
Keywords: Leadership